Pengaruh Reputation dan EWOM terhadap Repurchase Intention Konsumen pada E-Commerce - Faried Fajar; Diah Priharsari; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In the industrial revolution 4.0, companies are required to be able to carry out various innovations in order to adapt and compete with other companies. The use of technology in the community is also getting higher. E-commerce as the result of technology provides several benefits such as being able to improve information and also product sales transactions widely spread in the global market. In buying and selling activities, every company will certainly try to retain their customers. Increasing consumer repurchase intention towards the company's products or services is a challenge for every company. There are many factors that encourage consumers to make repeat purchases. Some factors those are discussed in this study are reputation, eWOM, and trust. This study aims to determine whether these factors affect consumer attitudes in repurchasing a product. The method used in processing the data in this study is SEM-CB. The use of the SEM-CB method is due to the confirmation of several theories related to this research. While the technique used to obtain data is by using a survey. After the survey, 326 data were obtained from respondents from e-commerce users. The results from this research are reputation, trust, and eWOM affected consumers' repurchase intentions.